2005
DOI: 10.1097/01.sap.0000185459.49434.5f
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Evaluation of Breast Symmetry and Shape Differences Using 3-Dimensional Images

Abstract: Natural breast asymmetry does exist, demonstrated objectively using 3-dimensional surfaces images. The left breast is on average larger than the right, with differences in size and shape being consistent but fairly unpredictable. It is important that we know baseline differences in breast symmetry prior to objectively analyzing results following esthetic and reconstructive breast surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 22 publications
5
74
0
2
Order By: Relevance
“…In fact, the proportion (36.3%) of respondents reporting breast asymmetry is significantly larger than the natural breast asymmetry seen among women without a history of breast cancer treatment (approximately 10% deemed clinically significant) (Losken et al 2005). Historically, exercise bras have not needed to accommodate for breast asymmetry, as studies of a general female population have found no significant difference in the vertical breast displacement between a right and left breast (McGhee, Steele, and Power 2007).…”
Section: Bra Sizementioning
confidence: 99%
“…In fact, the proportion (36.3%) of respondents reporting breast asymmetry is significantly larger than the natural breast asymmetry seen among women without a history of breast cancer treatment (approximately 10% deemed clinically significant) (Losken et al 2005). Historically, exercise bras have not needed to accommodate for breast asymmetry, as studies of a general female population have found no significant difference in the vertical breast displacement between a right and left breast (McGhee, Steele, and Power 2007).…”
Section: Bra Sizementioning
confidence: 99%
“…Moreover, in many cases the so called ''fixed'' scanners (for example the Minolta Vivid 900/910-Konica-Minolta Co, Ltd, Osaka, Japan) may not grant a complete subject's surface description in a single scan, requiring patient and/or scanner repositioning to execute multiple scans. 8,15,17 Hand-held scanners acquisition (for example the Polhemus FastScan-Polhemus, Colchester, VT, USA 13 ) on the contrary, may acquire the whole subject's surface in a single scan but lengthening, on the other hand, the acquisition duration, thus suffering in a higher way of the artifacts due to the involuntary and respiratory subject's movement.…”
Section: Introductionmentioning
confidence: 98%
“…In the adult population, some authors agree on this laterality fact [12,26], while others not [15,50,51]. When only considering studies using MRI as a measuring method [50,51], the tendency favors a larger right breast volume.…”
Section: Discussionmentioning
confidence: 96%
“…When performing aesthetic or reconstructive breast surgery, the plastic surgeon relies mostly on his/her aesthetic opinions and artistic skills as well as his/her experience [7]. Various methods to measure breast volume have been reported: Archimedian methods based on the water displacement principle [8][9][10], 3D thermoplastic casting [11][12][13], direct (from body surface) [14][15][16][17][18] or indirect (from 2D imaging such as photographs, mammograms or ultrasounds) [19][20][21] anthropometric measures, modern radiologic procedures (CT and MRI) and 3D body surface reconstruction obtained from biplanar images such as stereo photography, laser or phase shifted interferometry 3D surface scanning [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. To date, MRI measurements show the highest level of precision and are considered the gold standard for breast volume measurement [32,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%